Adaptation of Co-Cr copings made by induction casting and selective laser melting in CAD/CAM - Salvatierra Sevillano, Sheila Mariela (2020)
There are few studies comparing the ﬁt of cobalt-chromium copings (Co-Cr) manufactured by induction centrifugal casting technique and selective laser melting (SLM) in CAD/CAM. Objective: The purpose of this study was to evaluate in vitro the marginal and internal ﬁt of Co-Cr alloy unit copings on a chamfer termination line manufactured by induction centrifugal casting technique (CPCI) and selective laser melting (SLM) in CAD/CAM. Material and methods: Thirteen Co-Cr unit copings were made for each technique. Marginal and internal ﬁt were evaluated with the replica technique. Each sample was cross sectioned in the vestibular-palatine and mesio-distal direction, then observed in a stereomicroscope at a 40X magniﬁcation and measured at the cervical, axial and occlusal areas. Results: The marginal discrepancy of Co-Cr copings manufactured by the SLM technique was 38.1 μm and for the CPCI technique it was 42.22 μm without signiﬁcant diﬀerences (p > 0.05). The axial discrepancy for the copings manufactured by CPCI technique was 42.02 μm and for the SLM technique of 60.16 μm with signiﬁcant diﬀerence (P < 0.05). The occlusal discrepancy for the copings made by the CPCI technique was 101.94 μm and for the SLM technique was 232.13 μm with signiﬁcant diﬀerence (P <0.05). Conclusions: The marginal adaptation was similar for CPCI and SLM techniques but without statistically signiﬁcant diﬀerences. The internal adaptation was better for the CPCI technique than for the SLM technique with statistically signiﬁcant diﬀerences.